Dampak Faktor Ekonomi dan Non Ekonomi Terhadap Jumlah Anak di Indonesia: Analisis Data Demographic Health Survey 2017 - Munthe, MaySarah Qonita; Salsabila, Nasywa Nayifa; Kautsar, Achmad (Jurnal Ekonomi Kesehatan Indonesia, 2024)
Indonesia has a large population, with a declining annual growth trend. Economic and non-economic factors contribute to the desired number of children. This study uses the latest data from the 2017 Demographic and Health Survey (DHS) to analyze the relationship between these factors and the desired number of children. A logit model is employed to evaluate the probability of having more than two children.The findings indicate that higher economic status is associated with a lower likelihood of having more than two children. Women in the middle economic group are 7.1% less likely to have more than two children compared to women in the low-income group. Additionally, non-economic factors, such as education level, show significant associations. Women with higher education are 21.1% less likely to have more than two children compared to women with lower education levels. This highlights the importance of women's education as a key non-economic factor in managing population growth. The government could consider expanding access to education, such as providing scholarships specifically for women, to help them achieve higher education levels. This, in turn, could indirectly contribute to population control in Indonesia.